Removable dental prosthesis as periodontal treatment method - Adenan, Aprilia; Rusminah, Nunung (Padjadjaran Journal of Dentistry, 2007)
The objectives of prostheses are to restore mastication force, improve esthetics and maintain gingival health. The construction and function of prosthesis restoration are mutually interdependent with condition of periodontal tissues. A properly constructed prosthesis is an integral phase of complete treatment of periodontal disease in order to maintain periodontal tissues health. This paper reports case of a man aged 47 years who came to Dental Specialist Clinic in Oral and Dental Hospital Faculty of Dentistry Universitas Padjadjaran with chief complaint of mobility in almost all his teeth and they seems to look longer. The patient has no systemic disease and did not want his teeth to be extracted. Clinical and panoramic radiographic and laboratoris examinations has been done. During treatment, oclusal adjustment and splinting had been done on tooth 33,34,35 and tooth 44,43 also tooth 43,42 splinting with composite. The following treatment was the acrylic removable partial denture for upper jaw while mandible was fitted a frame denture which functioned as a semi permanent splint. One month post treatment, patien felt comfort and the denture was well functioning.